Share Subscription Ratio in Primary Markets - An Important Determinant for Identifying Good Stocks in Secondary Markets - Singh, J. K. (Indian Journal of Finance, 2009)
The investors in primary market often invest on the basis of recommendations given by brokerage houses or hearsay. However, even if the stock quotes at a price higher than what it has been issued for in the primary market, the net return when measured taking into account the amount of funds locked up in number of shares applied for and the number of shares allotted to an investor result in insignificant amount. The present study attempts to guide the investors in making money by purchasing the shares of certain companies immediately after its listing instead of trying their fate in primary market. The research study making use of various statistical techniques clearly evidences that the companies attracting good amount of investment from the Qualified Institutional Buyers tend to perform better in the long run as compared to the companies generally oversubscribed by retail investors.